The Relationship between Tumor Budding and Stromal Maturity with Tumor Characteristic and Survival in Patients Gastric Cancer - Kamrani, Ghodsieh; Noshadi, Nasibeh; Hosseini, Akramasadat; Nikbakhsh, Novin; Ranaee, Mohammad; Alizadeh-Navaei, Reza (Asian Pacific Journal of Cancer Biology, 2024)
Background: Considering the prognostic role of stromal maturity and tumor budding in various cancer types, along with the importance of gastric cancer as the fifth most prevalent cancer globally and the second leading cause of cancer-related mortality, this study aimed to investigate the impact of stromal maturity and tumor budding on patients with gastric cancer. Methods: In this retrospective cohort study, 91 patients diagnosed with gastric cancer and who underwent total gastrectomy in educational hospitals of Babol between 2016 and 2021 were evaluated. Slides corresponding to the deepest invasive tumor edge were reviewed by two independent pathologists to assess tumor budding and stromal maturity. Immunohistochemical staining with AE1/AE3 marker was used to correlate the results of tumor budding evaluation. Other pathological information was collected from patients’ records, and patient survival data were obtained through telephone follow-up. Data analysis was performed with SPSS V.22, utilizing T-test, Anova, Chi-square, Fisher’s exact test, Kaplan-Meier and Cox regression method. P-value <0.05 was considered as significant level. Results: The average survival of patients without tumor budding was 64.64 months, while the average survival of the low tumor budding group (less than 5 tumor buds in 10 microscopic fields at ×400 magnification) was 58.38 months, and the high tumor budding group (less than 5 tumor buds) had an average survival of 28.52 months (p=0.002). The average survival of patients with and without stromal maturity was 41.43 and 61.36 months, respectively (p=0.501). Conclusion: Tumor budding is an independent prognostic factor in gastric adenocarcinoma, but its predictive value is limited to the intestinal type of adenocarcinoma